2019
DOI: 10.1111/lam.13114
|View full text |Cite
|
Sign up to set email alerts
|

Empowering rice seedling growth by endophytic Bradyrhizobium sp. SUTN 9‐2

Abstract: Bradyrhizobium sp. strain SUTN9‐2 was confirmed as rice endophytic bacteria and also as rice growth promotion agent. SUTN9‐2 showed the capability of plant growth promotion characteristics, such as indole‐3‐acetic acid (IAA) and 1‐amino‐cyclopropane‐1‐carboxylic acid (ACC) deaminase productions and nitrogen fixation. In this study, the ability of SUTN9‐2 to stimulate rice growth was investigated at different stages with N‐free and NH4NO3 under in vivo condition. The rice dry weight and chlorophyll content coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…(Baldani et al 2000; Tran et al 2000; Govindarajan et al 2007), Bradyrhizobium sp. (Greetatorn et al 2019).…”
Section: Main Inoculated Cropsmentioning
confidence: 99%
“…(Baldani et al 2000; Tran et al 2000; Govindarajan et al 2007), Bradyrhizobium sp. (Greetatorn et al 2019).…”
Section: Main Inoculated Cropsmentioning
confidence: 99%
“…Bacteria-inoculated and uninoculated seedlings (three plants per test tube) were transferred and grown in a glass test tube (15 × 150 mm) as described by Greetatorn et al (2019). At 14 DAI, water stress was induced in the glass test tubes by replacing the Hoagland nutrient solution with a nutrient solution containing polyethylene glycol (PEG8000) (Santa Cruz Biotechnology, Inc., USA).…”
Section: Determination Of Ethylene Emissionsmentioning
confidence: 99%
“…Recently, rice endophytic Bradyrhizobium sp. SUTN9-2 was used to investigate growth promotion in rice seedlings; SUTN9-2 (wild type strain) was used as a bio-inoculant to promote rice growth at the seedling stage (seven and 14 days after inoculation) in Nfree and with NH 4 NO 3 in vivo conditions (Greetatorn et al 2019). In addition, our previous study on SUTN9-2 showed it improved the ACC deaminase activity through enhancing the symbiotic interaction, plant biomass and drought tolerance in the mung bean (Sarapat et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the genera that were more abundant when associated under unfertilized nature farming management play an important role in plant health and development. For example, Haliangium produces haliangicin as an antifungal compound that can inhibit the growth of a wide spectrum of fungi (Fudou et al, 2001), and Bradyrhizobum is known as PGPR and is able to fix atmospheric nitrogen (Greetatorn et al, 2019). A greater abundance of iron-reducing bacteria, including the Sideroxydans, Acidibacter and Anaeromyxobacter genera, was found under unfertilized nature farming conditions than under conventional farming conditions (Hori et al, 2010;Falagán and Johnson, 2014;Jin et al, 2017).…”
Section: Root Microbial Community Composition Between Unfertilized Nature Farming and Fertilized Conventional Farmingmentioning
confidence: 99%